Identifikasi Kebutuhan Bahasa Inggris Bagi Mahasiswa Teknik Sipil Politeknik Negeri Semarang - Sri Wahyuningsih Sulaiman; Suroso Suroso; Puji Wahyumi; Wildana Latif Mahmudi; Yusetyowati Yusetyowati (Bangun Rekaprima, 2016)
The goal of Semarang State Polytechnic is to produce skilled and professional graduates as middle expert technicians who have integrity, high self discipline, high responsibility and good proficiency of English skill for communication. In order to achieve the goal, it needs a good quality of curriculum which matches with industrial needs. To obtain empirical data to validate the English Language needs and skills, this research was done, and designed as a survey to achieve two aims: a).To identify the English language  skills are needed by civil engineering graduates to perform in the work environment. b).To identify the topics of ESP which are most required by the civil engineering graduates in their work environment. It was found that the English language skills which are most required by graduates in the work environment is speaking skill followed by the listening, reading and writing respectively, the speaking skill is to communicate with customers and consultants. The reading skill is to read contract document, tender calculation, specification of project work, instruction and writing skill is to write tender project document and proposal while listening is for communication and understanding presentation of a project work. Considering that the speaking is most needed in graduates work environment, it is suggested to give more time for speaking practice in English lesson, and give more material for writing project document. Hence, many essential topics which are not covered in the syllabus must be given time.Keywords: The goal, a good quality of curriculum, English language skills, graduates work environment.